Development of Magic Disc Media for Flat Shapes in Fourth Grade Elementary School - Nurdiani, Ninda Riana Rizqie; Sari, Arissona Dia Indah; Subayani, Nataria Wahyuning (JMEA : Journal of Mathematics Education and Application, 2025)
The type of development research with the Research and Development (RD) method using the ADDIE model through 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The number of students is 15 students. Based on an interview with the homeroom teacher of grade IV UPT SD NEGERI 135 GRESIK, the information obtained by the researcher regarding the problems in grade IV on the material of flat shapes is that in the process of learning Mathematics many have difficulty in understanding the material, one of which is that students have difficulty in the material of flat shapes, namely in understanding its characteristics. Based on the results of the study, the researcher produced a product in the form of magic disc media on the material of flat shapes. The results of the study from media validation obtained an average of 98%